2019
DOI: 10.1007/s13361-019-02291-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies on Cationization in MALDI-MS Employing a Split Sample Plate Set-up

Abstract: In the analysis of polymers by matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS), a commonly observed ionization pathway is cation adduct formation, as polymers often lack easily ionizable (basic/acidic) functional groups. The mechanism of this process has been hypothesized to involve gas-phase cation attachment. In previous experiments, a split sample plate set up has been introduced, enabling separate deposition of the components on individual MALDI plates. The plates are divided by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In MALDI-MSI of GPLs, alkali adduct ions are the most commonly observed type of ions in the positive-ion mode. Ion species of this type have been associated with thermal processes and the separation of preformed ion pairs, , while also the transfer of alkali-metal cations in the gas phase has been demonstrated. , Another important parameter predetermining a MALDI experiment is found in the morphology and composition of the matrix-analyte composite. ,, While for peptides and other hydrophilic analytes incorporation into the matrix crystal is fundamental, for lipophilic substances, such as GPLs, it is sufficient to diffuse into a matrix layer without co-crystallization. , …”
mentioning
confidence: 99%
“…In MALDI-MSI of GPLs, alkali adduct ions are the most commonly observed type of ions in the positive-ion mode. Ion species of this type have been associated with thermal processes and the separation of preformed ion pairs, , while also the transfer of alkali-metal cations in the gas phase has been demonstrated. , Another important parameter predetermining a MALDI experiment is found in the morphology and composition of the matrix-analyte composite. ,, While for peptides and other hydrophilic analytes incorporation into the matrix crystal is fundamental, for lipophilic substances, such as GPLs, it is sufficient to diffuse into a matrix layer without co-crystallization. , …”
mentioning
confidence: 99%
“…Fewer papers relating to the MALDI process appear to have been published during this review period than in the past, but some investigators are still keen to fully understand how MALDI works. A paper by Metternich et al (2019) has addressed the problem of where (on the target plate or in the gas phase) most of the ionization occurs. Using a split MALDI plate containing a polymer on one side and a IT, Ion trap; KLH, keyhole limpet hemocyanin; Kdo, 3-deoxy-D-manno-oct-2-ulosonic acid; Ko, D-glycero-D-talo-oct-2-ulosonic acid; L -, linear (as in linear-TOF); LAAPPI, laser ablation atmospheric pressure photoionization; Lac, lactose (Gal-β-(1→4)-Glc; LacNAc, N-acetyllactosamine (Gal-β-(1→4)-GlcNAc); LAESI, laser ablation electrospray ionization; LB, lysogeny broth; LC, liquid chromatography; LDI, laser desorption/ionization; Lec, lectin; Le x , Lewis antigen X; L-DOPA, L-3,4-dihydroxyphenylalanine; LID, laser-induced decomposition; LIF, laser-induced fluorescence; LNDFH, lacto-di-fucohexaose; LNFP, lacto-N-fucopentaose; LNnT, lacto-N-neotetraose; LNT, lacto-N-tetraose; LOD, limit of detection; LOQ, limit of quantitation; LOS, lipooligosaccharide; LPMO, lytic polysaccharide monooxygenases; LPS, lipopolysaccharide; LTQ, linear quadrupole ion trap mass spectrometer; MAA, methacrylic acid; mAb, monoclonal antibody; MALDI, matrix-assisted laser desorption/ionization mass spectrometry; MALDI-2, laser post-ionization MALDI; MALDESI, matrix-assisted laser desorption electrospray ionization; MAMS, microarrays for mass spectrometry; Man, mannose; ManNAc, N-acetylmannosamine; ManNAz, N-azidoacetylmanosamine; MBT, 2-mercaptobenzothiazole; MEL, mannosyl-erythritol lipid; MFDPPPs, polysaccharides from medicine and food dual purpose plants; MGMS, membrane glycolipid mass spectrum simulator; MIEA, 1-(2aminoethyl)-3-methyl-1H-imidazol-3-ium; MIRAGE, minimum requirement for a glycomics experiment; MNP, magnetic nanoparticle; MOF, metalorganic framework; MRI, magnetic resonance imaging; MRM, multiple reaction monitoring; MRSA, methicillin-resistant Staphylococcus aureus; MS, mass spectrometry; MSI, mass spectrometric imaging; MSIC, mass spectrometry imaging creation; MS n , successive MS fragmentation n times; MSNPs, magnetic silica nanoparticles; MTT, 3-methyl-1-p-tolyltriazene; MUC, mucin; MW, molecular weight; MurNAc, N-acetyl muramic acid; m/z, mass to charge ratio; NAPA, silicon nanopost arrays; N-CDs, nitrogen-doped carbon dots; Nd:YAG, neodymium-doped yttrium aluminium garnet (laser); NEDC, N-(1-naphthyl)ethylenediamine dihydrochloride; NETD, negative electron transfer dissociation; Neu5Ac, N-acetylneuraminic acid (sialic acid); Neu5Gc, N-glycolylneuraminic acid; NGAG, solid phase extraction of N-linked glycans and glycosite-containing peptides (method); NGL, neoglycolipid; NILM, nonionic liquid matrices; NISM, nonionic solid matrices; NIST, National Institute for Standards and Technology; NK, natural killer; NMR, nuclear magnetic resonance; 3-NPH, 3-nitrophthalhydrazide; NSCLC, non-small cell lung cancer; OA, osteoarthritis; ODS, octadecylsilyl; O-GPA, O-GlycoProteome Analyzer; OSu, N-hydroxysuccinimide ester; p (as in Glcp), pyranose form of sugar ring; PAMAM, poly (amidoamine); PAPAN,acrylonitrile; PBH, 1-pyrenebutyric hydrazide; PC, phosphatidylcholine; PCA, principal components analysis; PD, polydopamine; PDBe, Protein Data Bank in Europe; PE, phosphatidylethanolamine; PEG, polyethylene glycol; PEP, peptide; PEtN,phosphoethanolamine;PFBHA,3,4,5,-hydroxylamine; PFOA, perfluorooctanoic acid; PFOS, perfluorooctane sulfonate; PGC, porous graphitic carbon; PGM,...…”
Section: Theory Of the Maldi Processmentioning
confidence: 99%
“…Fewer papers relating to the MALDI process appear to have been published during this review period than in the past, but some investigators are still keen to fully understand how MALDI works. A paper by Metternich et al (2019) has addressed the problem of where (on the target plate or in the gas phase) most of the ionization occurs. Using a split MALDI plate containing a polymer on one side and a cationizing agent (copper, silver, or lithium) as its trifluoroacetate salt on the other, and with 2‐[4‐ tert ‐butylphenyl‐2‐methylprop‐2‐enylidene]‐malonitrile (DCTB, 1 ) as the matrix, they have shown that the cationization of the polymer occurs mainly in the gas phase.…”
Section: Theory Of the Maldi Processmentioning
confidence: 99%
“…For example, using solvent-free MALDI with the attachment of metal cations from alkali metal salts, the cationization efficiencies of polymer molecules have been probed. [116][117][118] Kuki et al 102 studied the chain length of PEG and PPG cationized by alkali metal ions using ESI-MS. The in-source collision-induced dissociation has helped to yield a neutral polyether and cation by dissociation of the sodiated, cesiated, and potassiated PEG and PPG without the formation of product ions resulting from the backbone cleavage.…”
Section: Characterization Of a Variety Of Polymer Types Using Metal S...mentioning
confidence: 99%